Relative age effect and long-term success in the Spanish soccer and basketball national teams - López de Subijana, C.; Lorenzo, J. (Journal of Human Kinetics, 2018)
The aims of this study were: i) to analyze whether relative age effect occurs in the athletes of the junior national teams and professional athletes in Spain in general and in soccer and basketball, and ii) to compare the long-term success of the players selected for the junior national team between these sports. The samples for this study were Spanish professional soccer (n = 461) and basketball (n = 250) players in the 2013-2014 premier league and players from the junior Spanish soccer (i.e., n = 273; U-17: n = 107; U-19: n = 166) and basketball (i.e., n = 240; U-18: n = 120, U-16: n = 120) teams that classified to play in the European Championships (from 2004 to 2013). Junior players (42.3%) were more frequently born in the 1st quarter of the year than the professional players (30.7%) (Chi2(3) = 30.07; p = .001; Vc = .157). This was found in both basketball (Chi2(3) = 12.2.; p = .007; Vc = .158) and soccer (Chi(3) = 20.13; p < .001; Vc = .166). Long-term success is more frequent in soccer, where 59.9% of the juniors selected for the national team played later in the premier league, while in basketball that percentage was 39.6% (?2(1) = 14.64; p < .001; Vc = .201). On the other hand, 79.4% and 39.8% of the professional soccer and basketball players had been previously selected for junior national teams (?2(1) = 60.2; p < .001; Vc = .386), respectively. The talent selection process should be reviewed as players born in the second half of the year have fewer opportunities to stand out.